If xy=0
assume that at least x or y=0
3(x-3)=0
therefor
3=0 or x-3=0
3=0 is false
therefor
x-3 mus equal zero
x-3=0
add 3 to both sides
x=3
Answer: I would say it as “Twenty-Two Point Seven Seconds” Hope this helps you
Step-by-step explanation:
2 goes into all the terms so;
2(-2x² + 7x - 3) now you could factor it:
2(-2x - 1)(x + 3)
Answer:
$1.21
Explanation:
What we know:
- $5.88=3 pounds of apples
- price went up by $0.75 per pound
First, we divide $5.88 by 3 to find out how much one pound of apples cost.
5.88/3
=1.96
Therefore, the new price of apples per pound is $1.96.
Because the old price of apples per pound was $0.75 cheaper, we subtract 0.75 from 1.96.
1.96-0.75
=1.21
Therefore, the old price of apples per pound was $1.21.
I hope this helps! Please comment if you have any questions.